Retirement and Labour Market Participation - BARRETT, ALAN (TILDA, 2011)
Labour market participation of older people is important from the perspective of the individual and the macroeconomy. At an individual level, participation in the labour market can be associated with increased resources and enhanced levels of life satisfaction if work is a source of positive social contact and engagement.
Fifty Plus in Ireland 2011. First results from the Irish Longitudinal Study on Ageing (TILDA)
PUBLISHED
Keywords: Social Policy; Economics; aging